Morphological, anatomical, secondary metabolites investigation and physicochemical analysis of Cistus creticus - Sahraoui, Rachid; Djellali, Souad; Chaker, Adel N (Pharmacognosy Communications)
Background: The aim of this work is to study the secondary metabolites and the physicochemical properties of Cistus creticus in addition to morphological characteristics for better knowledge. The literature indicates that this plant shows anti-inflammatory and antiviral properties. Locally it is used as sedative drink. Methods: The plant was collected from mountains surrounding the city of Batna (East of Algeria). Morphological characteristics of leaves and trichomes type were determined; leaves were then separated from stems, cleaned of impurities and dried for a few days at room temperature in shaded and ventilated place before being grounded to a powder. The powder was then subjected to the following analyses: i) phytochemical analysis using extraction with solvents of increasing polarity and qualitative determination of secondary metabolites and ii) chemical and physicochemical analysis where the humidity, percentage of ash and metals content are calculated. Results: The solvent extraction showed a high yield of polar compounds (5.76%) compared to apolar compounds (1.08%). Chemical tests revealed the presence of tannins, heterosides, triterpenes, flavonoids, and saponosides. In addition, it was found that the ash of the plant contains low amounts of toxic metals such as Hg and Pb which makes the plant safe to use. The anatomical study showed the presence of two types of trichomes: glandular and stellate.
Keywords: Folk medicine; Heavy metals; Phytochemistry; Solvent extraction; Trichomes